Keanekaragaman serangga pengunjung bunga mangrove di Gonda Mangrove Park Kabupaten Polewali Mandar, Provinsi Sulawesi Barat - Phika Ainnadya Hasan; Nurmiati Nurmiati (Perhimpunan Entomologi Indonesia, 2022)
Gonda Mangrove Park is a mangrove area that has been opened as a tourist area since 2014. This land function shifting is expected to affect the components of the mangrove ecosystem in the future. Insect can be used as bioindicators of an environment. The absence of preliminary data on the diversity of visitor insects in this area can be a limiting factor in the management and supervision of Gonda Mangrove Park as a tourist area. This study aims to analyse the diversity of flower-visiting insect of mangrove in Gonda Mangrove Park. The method used to observed the diversity of flower-visiting insect was scan sampling at three observation stations. Environmental parameters measured during the observation including air temperature and humidity, light intensity, and noise level. The results showed that there were five species of insect visitors, i.e., Trigona sp. (n = 148), Odynerus sp. (n = 121), Dolichoderus sp. (n = 53), Leptocorisa sp. (n = 28), and Xylocopa confusa Pérez (n = 2). Gonda mangrove park has a 1.25 Shannon-Wiener diversity index (H’), 0.77 Shannon evenness index (E), and 0.32 Simpson dominance index (C). Noise from tourist negatively correlated to the abundance of flower-visiting insects of mangrove (r = -0.95; p = 0.01).